Constitutive modelling of sheet-layered lamination stacks - Baloglu, Maximilian Volkan; Willner, Kai (Proceedings in Applied Mathematics and Mechanics, 2018)
Sheet‐layered lamination stacks found in electric motors as rotor and stator are a challenging task in structural mechanics due to their special design. The manufacturing process determines the nature of the microstructure resulting in the presence of bonding varnish or frictional contact between the individual metal sheets. For the latter case, a penalty method in normal and tangential direction can be used to capture the contact interactions of single plates. In combination with homogenization techniques, a transversely isotropic surrogate material model with a corresponding strain energy density can be identified. In this paper, the focus lies on the influence of the penalty parameters on the elastic quantities of the constitutive equation.<br

Determination of equivalent transversely isotropic material parameters for sheet-layered lamination stacks - Baloglu, Maximilian Volkan; Ziegler, Marco; Franke, Jörg; Willner, Kai (Mechanical Systems and Signal Processing, 2020)
This paper covers the accurate prediction of equivalent homogenized material parameters for sheet-layered lamination stacks, which are located in rotors and stators of electric motors. Modeling the structural and dynamic behavior of these parts is a challenging task due to the special layered design of these stacks, with a huge influence of the applied joining technology, here a full-surface bonding. For the derivation of equivalent transversely isotropic material parameters, three procedures, namely the rule of mixture, an analytical and numerical homogenization, are compared eventuating in only minor differences between them. The investigations show that rather the input parameters for these averaging methods, i.e. the individual material parameters of each layer, are crucial for an accurate modeling. Experimental tests are carried out on coated sheet laminations to determine the initially unknown bonding varnish thickness with two different measurement methods, the 3D laser scanning microscopy and instrumented indentation testing, resulting in almost equivalent and reasonable values. The capability of the ab initio deduced material parameters is demonstrated by comparing an experimental and numerical modal analysis of a sample lamination stack showing an almost perfect agreement. By this, it is also revealed that a varnish Young's modulus measured by nanoindentation is overestimated from a macroscopic point of view. Damping parameters of a bonded lamination stack are determined with the help of the experimental modal analysis showing a relatively low damped system.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Homogenization; Lamination stack; Laser scanning microscopy; Material modeling; Modal analysis; Nanoindentation

Determination of material parameters for a sheet‐layered lamination stack - Baloglu, Maximilian Volkan; Willner, Kai (Proceedings in Applied Mathematics and Mechanics, 2017)
The numerical simulation of sheet‐layered lamination stacks is a challenging task in structural mechanics due to the layout of these components. Depending on the manufacturing process, these sheets are either linked together with the help of a bonding varnish or are just packed up and basically free to slip inside of the stack, which can result in a nonlinear deformation behavior. To avoid a full FE‐simulation incorporating every layer, homogenization can be applied to identify a surrogate material model to achieve the desired accuracy by gaining performance. In this paper, a transversely isotropic material model is analytically formulated for a lamination stack with isotropic sheets in contact, which is captured with the help of a linear penalty method. The resulting stress‐strain relation is compared to results obtained by a numerical homogenization.
Keywords: lamination stack; homogenization; material modelling; contact mechanics

Evaluation of the surface fatigue behavior of amorphous carbon coatings through cyclic nanoindentation - Weikert, Tim; Wartzack, Sandro; Baloglu, Maximilian Volkan; Willner, Kai; Gabel, Stefan; Merle, Benoit; Pineda, Fabiola; Walczak, Magdalena; Marian, Max; Rosenkranz, Andreas; Tremmel, Stephan (Surface & Coatings Technology, 2021)
Diamond-like carbon (DLC) coatings, frequently used to reduce wear and friction in machine components as well as on forming tools, are often subjected to cyclic loading. Doping of DLC coatings with metals or metal carbides as well as the usage of multilayer architectures represent promising approaches to enhance toughness, which is beneficial for the coatings’ behavior under cyclic loading. In this study, we utilized cyclic nanoindentation to characterize the tribologically induced surface fatigue behavior of single-layer tungsten-doped (a-C:H:W) and multilayer silicon oxide containing (a-C:H:Si:O/a-C:H)25 amorphous carbon coatings under cyclic loading. Columnar growth was observed for both coatings by focused ion beam microscopy and scanning electron microscopy, while the multilayer architecture of the (a-C:H:Si:O/a-C:H)25 coating was verified by the silicon content using glow-discharge optical emission spectroscopy. In cyclic nanoindentation of the (a-C:H:Si:O/a-C:H)25 multilayer coating, stepwise small changes in indentation depth were observed over several indentation cycles. The surface fatigue process of the single-layer a-C:H:W covered a smaller number of indentation cycles and was characterized by an early steep increase of the static displacement signal. Microscopical analyses hint at grain deformation, sliding at columnar boundaries, and grain detachment as underlying fatigue mechanisms of the a-C:H:W coating, while the (a-C:H:Si:O/a-C:H)25 multilayer coating showed transgranular crack propagation and gradual fracturing. In case of the (a-C:H:Si:O/a-C:H)25 multilayer coating, superior indentation hardness (HIT) and indentation modulus (EIT) as well as a higher HIT3/EIT2 ratio suggest a higher resistance to plastic deformation. A high HIT3/EIT2 ratio, being an indicator for hindered crack initiation, combined with the capability of stress relaxation in soft layers contributed to the favorable surface fatigue behavior of the (a-C:H:Si:O/a-C:H)25 multilayer coating observed in this cyclic nanoindentation studies.
Keywords: Diamond-like carbon; Cyclic nanoindentation; Surface fatigue; Multilayer architecture

Influence of the Constitutive Contact Law on the Anisotropic Material Parameters of Sheet-Layered Lamination Stacks - Baloglu, Maximilian Volkan; Willner, Kai (2018 8th International Electric Drives Production Conference (EDPC), 2018)
The specific design of components like rotor and stator as sheet-layered lamination stacks results in a structural behavior that is heavily dependent on the sheet interactions on the microscale. Due to the manufacturing process, these thin laminations may be just stacked and held together e.g. by welding or clamps, such that frictional contact of rough surfaces between single sheets is taking place and significantly affects the overall deformation behavior. Here, the elastic anisotropic, more precisely transversely isotropic, material parameters describing these lamination stacks are identified with the help of the homogenization taking efficiently care of the microstructure. For this purpose, different constitutive contact laws in normal direction capturing the sheet interactions by a penalty formulation and their effect on the macroscopic quantities are presented to emphasize the importance of this model parameter. Furthermore, it is shown that the derived stress-strain relation is identical to results of a numerical homogenization, where a representative volume element is simulated by the Finite-Element method incorporating Zero-Thickness elements for the contact simulation. The numerical results are finally compared to experiments showing a good accordance.<br
Keywords: lamination stack; homogenization; constitutive modeling; material modeling; contact mechanics

In Situ Measurements of Interfacial Contact Pressure During Impact Hammer Tests - Seeger, Benjamin; Butaud, Pauline; Baloglu, Maximilian Volkan; Du, Fei; Brake, Matthew; Schwingshackl, Christoph (Nonlinear Dynamics, Volume 1; Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018, 2018)
Understanding the nonlinear dynamical contact interactions within joints is crucial for understanding and predicting the dynamics of assembled structures. In spite of this, most experimental investigations focused on the global vibration behavior, since the local interactions at the interface cannot be observed with standard techniques. In the present work, an advance contact pressure measurement system is used in a unique way to analyze, in situ, the interfacial contact pressures and the contact area inside a bolted lap joint connecting two beams (Brake-Reuß beam). An important feature of the measurement system is that it is designed for frequency ranges including the typical vibration frequency of the Brake-Reuß beam’s first eigenmode, and thus permits measurement under dynamic excitation. The dynamics of the contact pressures were investigated with different bolt torque levels and with different excitation levels. The experiments found that significant variations of the contact state occurred and that the contact pressure measurement system could adequately resolve this effect. The influence of the measurement system itself on the global vibration response of the Brake-Reuß beam was shown to be tolerable.<br
Keywords: Assembly; Lapjoint; Nonlinear; Experimental; Pressure sensor

Material modelling of a sheet-layered lamination stack by homogenization - Baloglu, Maximilian Volkan; Willner, Kai (Proceedings in Applied Mathematics and Mechanics, 2016)
In electrical machines, sheet-layered lamination stacks play an important role for the mechanical behavior of the system. Especially the interlayer between individual sheets and their interaction have a severe influence on the structure. In the context of performance and computational effort, it is desirable to avoid a full FE simulation of a lamination stack with every single sheet. Therefore, homogenization techniques are presented to identify a transversely isotropic surrogate material model, while Zero-Thickness elements are utilized during this process to cover the interplay of single sheets. (© 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)
Keywords: lamination stack; numerical homogenization; material modelling; contact mechanics

Numerical homogenization and simulation of a lamination stack - Baloglu, Maximilian Volkan; Willner, Kai (2016 6th International Electric Drives Production Conference (EDPC), 2016)
Parts of electric motors and transformers are composed of sheet-layered lamination stacks, which heavily influence the mechanical properties of such devices. Especially the interaction of individual sheets by direct contact or the presence of bonding varnish may cause a nonlinear deformation behavior such that these effects have to be included in a FE-simulation. Here, homogenization techniques are presented to ensure computational efficiency by avoiding a full numerical simulation with every single sheet and to cover simultaneously the real physical behavior by identifying a linearized transversely isotropic surrogate material model. During this homogenization process, the interlayer between two sheets is incorporated by Zero-Thickness element
Keywords: Contact Mechanics; Lamination Stack; Numerical Homogenization; Material Modelling

Unconventional Discretisations of the Temperature Equation in Earth Mantle Dynamics - Baloglu, Maximilian Volkan; Nadjafabadi Farahani, Mohammad Hassan; Rettinger, Christoph; Vogel, Constantin (2014)
Due to the high Péclet-number occurring in Earth mantle dynamics, the energy equation can be approximated by a pure advection equation for the temperature. However, conventional approaches like the Finite Element Method introduce undesired diffusion. Therefore, the task of our BGCE Honours Project is to develop and evaluate unconventional discretisations of the temperature equation that tackle the problem of artificial diffusion. We come up with two different methods: One is based on the Bresenham algorithm stemming from computer graphics. It uses offset values to determine the advection direction of the temperature. The other method features a Lagrangian description of the problem. We achieve this by deploying particles that incorporate temperature values and are advected only by the underlying velocity field. Simulations in one- and two-dimensional domains reveal inherent shortcomings of the Bresenham Method which cannot be overcome by several attempts. On the other hand, the Lagrangian Method yields promising results that can be further improved by additional treatments. We extend the Lagrangian Method to work on triangle and tetrahedron grids to offer an interface to the implementation of the Earth mantle dynamics solver of the Terra-Neo project. Additional advantages of the proposed method are the parallelisation capability, a straight-forward extension for advecting other physical quantities and the possible inclusion of physical diffusion in an operator-splitting approach.